Multiplex PCR system for rapid detection of pathogens in patients with presumed sepsis - a systemic review and meta-analysis. - Shy-Shin Chang; Wen-Han Hsieh; Ting-Shou Liu; Si-Huei Lee; Chih-Hung Wang; Hao-Chang Chou; Yee Hui Yeo; Ching-Ping Tseng; Chien-Chang Lee (PLoS ONE)
Background Blood culture is viewed as the golden standard for the diagnosis of sepsis but suffers from low sensitivity and long turnaround time. LightCycler SeptiFast (LC-SF) is a real-time multiplex polymerase chain reaction test able to detect 25 common pathogens responsible for bloodstream infections within hours. We aim to assess the accuracy of LC-SF by systematically reviewing the published studies. Method Related literature on Medline, Embase, and Cochrane databases was searched up to October 2012 for studies utilizing LC-SF to diagnose suspected sepsis and that provided sufficient data to construct two-by-two tables. Results A total of 34 studies enrolling 6012 patients of suspected sepsis were included. The overall sensitivity and specificity for LC-SF to detect bacteremia or fungemia was 0·75 (95% CI: 0·65-0·83) and 0·92 (95%CI:0·90-0·95), respectively. LC-SF had a high positive likelihood ratio (10·10) and a moderate negative likelihood ratio (0·27). Specifically, LC-SF had a sensitivity of 0·80 (95%CI: 0·70-0·88) and a specificity of 0·95(95%CI: 0·93-0·97) for the bacteremia outcome, and a sensitivity of 0·61 (95%CI: 0·48-0·72) and a specificity of 0·99 (95%CI: 0·99-0·99) for the fungemia outcome. High heterogeneity was found in the bacteremia outcome subgroup but not in the fungemia outcome subgroup. Conclusion LC-SF is of high rule-in value for early detection of septic patients. In a population with low pretest probability, LC-SF test can still provide valuable information for ruling out bacteremia or fungemia.